Plato’s theory of Numbers-Principles and its importance to the philosophical reconstruction of Plato’s dialects (Revista Archai, 2011)
At present, we have at our disposal a firm and broad elucidation and reconstruction of Plato’s theories of principles and ideal numbers in their historical and philological aspects. Nevertheless, until now the philosophical discussion about the relevance and meaning of these theories as to their possible contribution to the interpretation of Plato’s late dialectic remains open. In this paper, I will try to show those ideal numbers, including the principles to which they are dependent on, make up the structure of ideas and provide an explanation of their own order as well as of their organization according to genus-species patterns.